Lejeuneaceae (Marchantiophyta) of Batang Gadis National Park, North Sumatra, Indonesia, with new records for Sumatra and Indonesia - NURMAINI GINTING; NURSAHARA PASARIBU; ETTI SARTINA SIREGAR; SYAMSUARDI SYAMSUARDI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Ginting N, Pasaribu N, Siregar ES, Syamsuardi. 2026. Lejeuneaceae (Marchantiophyta) of Batang Gadis National Park, North Sumatra, Indonesia, with new records for Sumatra and Indonesia. Biodiversitas 27 (5): d270503. https://doi.org/10.13057/biodiv/d270503. Lejeuneaceae (Marchantiophyta) represents one of the most diverse families of liverworts in tropical regions, yet its distribution and diversity in Sumatra remain poorly documented. This study provides the first documented checklist of Lejeuneaceae from Sopotinjak, Batang Gadis National Park (BGNP), North Sumatra, Indonesia, an ecologically important montane forest area located within the northern Sumatran biogeographic zone. Field surveys were conducted from July to November 2022, and both corticolous and epiphyllous specimens were collected across altitudes of 1,205-1,531 meter above sea level (masl). Morphological observations and species identification were carried out using standard bryological techniques under light microscopy and by comparison with regional taxonomic keys. A total of 31 species belonging to 12 genera and two subfamilies were recorded. Drepanolejeunea was the most species-rich genus, followed by Lejeunea, Cololejeunea, and Lopholejeunea. Five species are reported as new distributional records, including three new to Indonesia (Cololejeunea surinamensis, Colura inuii, and Diplasiolejeunea rudolphiana) and two new to Sumatra (Drepanolejeunea angustifolia and Cheilolejeunea falsinervis). Most species were epiphyllous, reflecting the humid and shaded montane forest conditions of BGNP. These findings highlight BGNP as an important reservoir of Lejeuneaceae diversity in western Malesia and expand the known distribution of several taxa. The study also underscores the need for further systematic and quantitative surveys to better understand species richness, ecological patterns, and conservation significance of bryophyte communities in Sumatra.